PERLINDUNGAN HUKUM TERHADAP KREDITUR KONKUREN DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (PKPU) PT. MEGA PESANGGRAHAN INDAH (ANALISIS PUTUSAN NO. PERKARA: 259/Pdt.Sus-PKPU/2020/PN.Niaga.Jkt.Pst) - Steven Abrahan, (2022)
One of the property development companies in Indonesia, namely PT. Mega Pesanggrahan Indah. Referring to "Central Jakarta Commercial Court Decision Number 259/ Pdt. SusPKPU/2020/PN.Niaga.JktPst Year 2020 PT. Mega Pesanggrahan Indah", creditor from PT. Mega Pesanggrahan Indah, namely CV. Virgo Mandiri Sakti submitted a PKPU application to the Central Jakarta Commercial Court because the debt that was due was unable to be paid by the debtor to the creditor. The PKPU application letter was sent to the applicant on September 2, 2020 to the Central Jakarta Commercial Court. The applicant has been declared by the Commercial Court on September 22, 2020 in the Temporary PKPU. Then, the first creditors meeting was held on November 2, 2020 with the agenda for the Peace Plan Discussion and voting for PT. Mega Pasanggrahan Indah, in which case in the implementation of the meeting there were still creditors who did not agree on the peace proposal. Through law and the government, unsecured creditors in this case are consumers of flats, must obtain legal protection if the developer is unable to fulfill the agreement in the Sale and Purchase Binding Agreement (PPJB). The legal protection referred to is carrying out deliberation for consensus. If consensus cannot be reached, the consumer has the right to file a lawsuit in a general court or if he takes a route to an external court, generally through arbitration.